Block based semi-global alignment scheme for the analysis of Given DNA sequences - Basu, K.; Sriraam, N.; Richard, R. J. A. (2006)
Pair wise sequence alignment scheme has been emerged as an efficient computational tool to find region of similarity among sequences of proteins and nucleic acids. As new disease causing viruses are emerging rapidly, new alignment schemes with the advent of fast computers have gained its importance recently. In this paper, we have proposed a block based semi-global alignment scheme to evaluate the optimal alignment between any given two DNA sequences. DNA sequences are divided into blocks of equal length and alignment between the block is determined using dynamic programming. The performances are evaluated in terms of overall matrix score and percentage of similarity. It is inferred from the results, that higher the percentage of similarity between any two blocks, it may code for the same protein/amino acids. The computational complexity of the proposed algorithm is much less compared to that of the general global alignment scheme with O (M, N).